Unfolding a sequence of sensory influences and interactions in the development of functional brain laterality - Rogers, Lesley J. (Frontiers in Behavioral Neuroscience, 2023)
Evidence of sensory experience influencing the development of lateralized brain and behaviour is reviewed. The epigenetic role of light exposure during two specific stages of embryonic development of precocial avian species is a particular focus of the research discussed. Two specific periods of light sensitivity (in early versus late incubation), each depending on different subcellular and cellular processes, affect lateralized behaviour after hatching. Auditory and olfactory stimulation during embryonic development is also discussed with consideration of their interactions with light-generated visual lateralization.